x = [ 3 ± √(9 + 16) ] / 4
x = [ 3 ± 5 ] / 4
x = 2 , x = - 1 / 2
2007-11-22 06:54:06
·
answer #1
·
answered by Como 7
·
1⤊
1⤋
i dont comprehend on the subject of the quadratic formulation (havent gotten there in my algebra classification) yet you're able to do it by way of the zeros. 2x2 - 3x - 2 = 0 (first get in the customary form, Ax2 + Bx + C. element out the trinomial) (2x + a million ) (x - a million) = 0 (separate the equation so each and every binomial equals 0) (2x + a million) = 0 OR (x - a million) = 0 (resolve each and every for x) 2x + a million = 0 - a million - a million 2x = -a million /2 /2 x = -a million/2 x - a million = 0 + a million + a million x = a million X = -a million/2 AND X = a million <-------- answer!
2016-12-10 03:38:46
·
answer #2
·
answered by veloso 4
·
0⤊
0⤋
a = 2, b = -3 and c = -2
x = (-b +/- Sqrt(b^2 - 4ac))/2a
= (3 +/- sqrt( 9 + 16)) / 4
= (3 +/- 5)/4
= 2 or -1/2
check the eq can be factorize into (2x+1)(x-2)=0
giving x = 2 or -1/2
2007-11-22 06:54:49
·
answer #3
·
answered by norman 7
·
0⤊
0⤋
2x^2-3x-2=0
Discriminant = (-3)^2 -4(-2)(2) = 9 +16 = 25 = 5^2
x1 = (3 -5)/4 = -1/2
x2 = ( 3 +5)/4 = 2
2007-11-22 06:51:27
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Quadratics are in this format: ax^2+bx+c=0 all you need to do is substitute into this equation:
-b+or-(√(b^2-4ac))/2a
So
3+or-(√(25))/4
= (3+or-5)/4
2 or -1/2
2007-11-22 06:57:56
·
answer #5
·
answered by chem math phy ICT man 2
·
0⤊
1⤋
2x^2 -3x -2 =0 formula = squared root of: (((b^2 - 4(ac)) +/-(b))/2a)
squared root of: (-3^2) -4(2)(-2) = squared root of 25 = 5
5 - (-3) = 8 /4 = 2
5 +(-3) = 2 / 4 = 0.5
x = 2
x= -0.5
2007-11-22 09:08:15
·
answer #6
·
answered by Eduardo (lalo) Leal 2
·
0⤊
0⤋
ax^2+bx+c
-b/2a + and - Square root of b^2 - 4ac then divide by 2a.
3/2(2) + and - 6 - -16
square root 22 then divide that by 2
3/4 + that answer
3/4 - that answer
there are two answers for your x.
2007-11-22 06:51:00
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
2x^2-3x-2=0
(x-2)(2x+1)=0
x=2
or
x=-1/2
2007-11-22 06:55:14
·
answer #8
·
answered by THE WAY I AM 2
·
0⤊
0⤋
x = [-(-3) ± √(-3² - 4(2)(-2))]/2(2)
= [3 ± √(25)]/4
= [3 ± 5]/4
x₊ = 0.75 +1.25 = 2
x₋ = 0.75 - 1.25 = -0.5
2007-11-22 06:53:37
·
answer #9
·
answered by DWRead 7
·
0⤊
0⤋